Awarness Of Prayer Worship In A Psychological Perspective (Analysis of the Development of Elementary School Children to Adults) - Mita Kurnia Ningrum (Linguanusa : Social Humanities, Education and Linguistic, 2023)
The younger generation, which is starting to get stuck with the busyness of technology, makes them unaware that they have been stuck in a pattern that, among other things, actually takes up their time and energy. Several school assignments, work, and interest in contemporary technology often trigger a loss of balance between the world and the afterlife. Awareness of praying is essential because it directly impacts the mentality of every Muslim; this is also supported by Fawler's statement that faith and firmness are crucial points without which humans are useless. The purpose of this research is to discover the psychological development of prayer awareness from elementary school age to adulthood, which in his research refers to the theory of faith formation. In this study, the method used was qualitative research with a psychological approach which took 8 participants, each representing each level of elementary, junior high, high school, and early adulthood. The data collectiontechnique used by researchers used interview and observation techniques and continued analyzing the data through data reduction procedures, presenting data, and providing conclusions. The results of this study show that the understanding related to prayer awareness in each participant that the researcher met shows that they have an understanding that is appropriate for each age, whereas, for elementary school age, they still understand prayer related to allusions and also rewards for its implementation, while at junior high school age up to the age of Early adults already fully understand the concept of prayer awareness. With this in mind, the research conducted includes the development of a person's faith according to the stages, making it easier for parents and teachers to provide age appropriate stimuli. This is to give a positive impression of the worship activity, especially on one's understanding of the implementation of prayer.